EXPLICIT SOLUTION OF THE LP-MODEL OF THE NEURAL NETWORK LEARNING PROBLEM - Karčicka, Dimitra; Jovančevski, Gjorgji (Matematichki Bilten, 1998)
In [2] the neural network learning problem was formulated as the following LP-problem:Find \(x_j \geq 0,\ j=1,\ldots,n+1\) which satisfy the \(n^2+1\) constraints:\[x_i-a_{si}x_s+h_ix_{n+1}\geq 0,\qquad i e s,\quad i,s=1,\ldots,n\]\[x_i-x_{n+1}\geq 0,\qquad i=1,\ldots,n\]\[x_1+x_2+\cdots+x_n=1\]and maximize the linear form \(z=x_{n+1}\);all the \(a_{si}\), \(h_i\), \(0\leq a_{si}